2021
DOI: 10.1242/dmm.048952
|View full text |Cite
|
Sign up to set email alerts
|

Recessive, gain-of-function toxicity in an APOL1 BAC transgenic mouse model mirrors human APOL1 kidney disease

Abstract: People of recent sub-Saharan African ancestry develop kidney failure much more frequently than other groups. A large fraction of this disparity is due to two coding sequence variants in the APOL1 gene. Inheriting two copies of these APOL1 risk variants, known as G1 and G2, causes high rates of focal segmental glomerulosclerosis (FSGS), HIV-associated nephropathy and hypertension-associated end-stage kidney disease. Disease risk follows a recessive mode of inheritance, which is puzzling given the considerable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 82 publications
4
44
1
Order By: Relevance
“…This hypothesis was supported by recent reports that transgenic overexpression of APOL1 risk alleles in mouse podocytes or GECs caused podocytopathy, endotheliopathy, glomerulopathy, and clinical manifestations of kidney failure (10)(11)(12)(13)(14). These murine disease models suggest that the mechanism that underlies COVID-19-induced APOL1 expression would be a potential therapeutic target for COVAN.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This hypothesis was supported by recent reports that transgenic overexpression of APOL1 risk alleles in mouse podocytes or GECs caused podocytopathy, endotheliopathy, glomerulopathy, and clinical manifestations of kidney failure (10)(11)(12)(13)(14). These murine disease models suggest that the mechanism that underlies COVID-19-induced APOL1 expression would be a potential therapeutic target for COVAN.…”
Section: Introductionmentioning
confidence: 54%
“…Dose-dependent APOL1 cytotoxicity was also reported in similar cell-based systems (34). Moreover, APOL1 transgenic mouse models have not only validated the causal link between APOL1 risk alleles and podocyte injury but have demonstrated that the degree of podocytopathy correlated with APOL1 expression levels (10,(12)(13)(14)35). Our discovery that 8 of 9 patients with COVAN demonstrated robust glomerular APOL1 expression relative to control individuals and the evidence that expression of endogenous APOL1 risk alleles causes podocytopathy in human kidney micro-organoids support the causal link between APOL1 and podocytopathy.…”
Section: Discussionmentioning
confidence: 78%
“…They also showed that the heterozygous mice (G0/G1 or G0/G2) had greater proteinuria response than hemizygous mice (G1/-or G2/-), suggesting that APOL1-G0 does not rescue -G1 or -G2 allele toxicity. Further, mice with a multicopy G2 transgene (G2 multi /G2 multi ) showed the greatest proteinuria response with worst prognosis, supporting the recessive nature of APOL1nephropathy and the notion that disease is a function of the expression level of APOL1 risk variant (21).…”
Section: Micementioning
confidence: 78%
“…We did not explore the therapeutic potential of ΔMSALFL in a bacterial artificial chromosome (BAC) transgenic murine model harboring either the wild-type (G0), G1 or G2 forms of human APOL1 ( McCarthy et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%